White Matter Abnormalities in Children with HIV Infection and Exposure - Jankiewicz, Marcin; Holmes, Martha J.; Taylor, Paul A.; Cotton, Mark F.; Laughton, Barbara; van der Kouwe, André J. W.; Meintjes, Ernesta M. (Frontiers in Neuroanatomy, 2017)
Due to changes in guidelines and access to treatment, more children start combination antiretroviral therapy (ART) in infancy. With few studies examining the long-term effects of perinatal HIV infection and early ART on neurodevelopment, much is still unknown about brain maturation in the presence of HIV and ART. Follow-up studies of HIV infected (HIV+) children are important for monitoring brain development in the presence of HIV infection and ART. We use diffusion tensor imaging (DTI) to examine white matter (WM) in 65 HIV+ and 46 control (HIV exposed uninfected (HEU) and HIV unexposed uninfected (HU)) 7-year-old children. This is a follow up of a cohort studied at 5 years, where we previously reported lower fractional anisotropy (FA) in corticospinal tract (CST) and mean diffusivity (MD) increases in inferior/superior longitudinal fasciculi (ILF/SLF), inferior fronto-occipital fasciculus (IFOF) and uncinate fasciculus (UF) in HIV+ children compared to uninfected controls. In addition, we also found a difference in FA related to age at which ART was initiated. At 7 years, we found two regions in the left IFOF and left ILF with lower FA in HIV+ children compared to controls. Higher MD was observed in a similar region in the IFOF, albeit bilaterally, as well as multiple clusters bilaterally in the superior corona radiata (SCR), the anterior thalamic radiation (ATR) and the right forceps minor. Unlike at 5 years, we found no impact on WM of ART initiation. In HEU children, we found a cluster in the right posterior corona radiata with higher FA compared to HU children, while bilateral regions in the CST demonstrated reduced MD. At age 7, despite early ART and viral load (VL) suppression, we continue to observe differences in WM integrity. WM damage observed at age 5 years persists, and new damage is evident. The continued observation of regions with lower FA and higher MD in HIV+ children point to disruptions in ongoing white matter development regardless of early ART. Lastly, in HEU children we find higher FA and lower MD in clusters in the CST tract suggesting that perinatal HIV/ART exposure has a long-term impact on WM development.